A literature review on behavioral attributes of yoga postures and cognition - Ankit Gupta; Ram Kumar Gupta (Wolters Kluwer Medknow Publications, 2021)
Background: Hatha Yoga is the science of training one's mind and body through the practice of shatkarma, asana, pranayama, mudra, and samadhi. The objective of this literature review is to provide a theoretical rationale to identify (a) the specific attribute of the yoga poses which have been used in yoga protocol of various studies but not explicitly explored and (b) the minimum time required to hold a posture to bring the corresponding change in the performance among aforesaid cognitive function(s). Materials and Methods: Keywords such as yoga and cognition, yoga and working memory, yoga posture and cognition, and yoga and attention have been used to retrieve 24 empirical studies from Google Scholar. Those studies which have included only the yoga poses (asanas) as part of the yoga intervention in improving the cognitive functions were included in the review. Results: Traditions of Yoga such as Hatha and Iyengar Yoga emphasizes on postural alignment and accuracy, these asanas improve a variety of psychological, physiological, and cognitive functions. One study showed an improvement in cognitive functions and in another study, yoga practitioners showed improved reaction time. Conclusion: Due to inadequate empirical studies on yoga posture and cognition, it is not recommended to definitively conclude about the role of said attributes in improving cognitive performance. Future studies should involve longitudinal and randomized designs, large sample size, and homogeneous sample in terms of age-, gender-, and disease-specific population. The details of the studies are described in the manuscript.